Global warming and heat waves risks for cardiovascular diseases - Caldeira, Daniel (2023)
Global warming is a result of the increased emission of greenhouse gases. This climate change consequence threatens society, biodiversity, food and resource availability. The consequences in health involve the increased risk of cardiovascular (CV) disease and cardiovascular mortality. In this position paper we summarize the data from the main studies that assessed the risks of temperature increase or heat waves in CV events (CV mortality, myocardial infarction, heart failure, stroke, and CV hospitalizations), as well as the data concerning air pollution as an enhancer of temperature-related CV risks. The data currently supports that global warming/heat waves (extreme temperatures) are cardiovascular threats. Achieving the neutrality in the emissions to prevent global warming is essential and it is likely to have an effect in the global health, including the cardiovascular health. Simultaneously, urgent step is required to adapt the society and individual to this new climate context potentially harmful for the cardiovascular health. Multidisciplinary teams should plan and intervene in heat-related healthcare and advocate for environmental health policy change.